Infectious Diseases Caused by Bacteria and Viruses and the Challenge of Antibiotic Resistance - Bian, Rumo (Exploring Science Academic Conference Series, 2026)
The types of infectious diseases and the number of patients have increased significantly, posing a serious threat to global medical health. In particular, the rise in antibiotic resistance is making bacterial infections more difficult to treat. It is preci sely because of the abuse of antibiotics that bacteria have rapidly developed drug resistance, especially in the case of multidrug -resistant strains, that traditional antibiotic therapy is gradually becoming ineffective. In addition, the rapid mutation of the virus also brings challenges to vaccine development. Taking SARS-CoV-2 as an example, its mutation reduces the effectiveness of the vaccine and increases the complexity of prevention and control. Bacteria and viruses have significant differences in structure and metabolism, which determine their respective treatment methods. Bacteria can be treated with antibiotics, while viruses must rely on vaccines and antiviral drugs to control them. Therefore, scientists are trying to address these challenges by studying bacterial resistance mechanisms, optimizing the composition of HPV vaccines, analyzing the impact of SARS -CoV-2 mutations, and exploring alternative treatments to antibiotics.